9x-12y+6=0

Simple and best practice solution for 9x-12y+6=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x-12y+6=0 equation:


Simplifying
9x + -12y + 6 = 0

Reorder the terms:
6 + 9x + -12y = 0

Solving
6 + 9x + -12y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + 9x + -6 + -12y = 0 + -6

Reorder the terms:
6 + -6 + 9x + -12y = 0 + -6

Combine like terms: 6 + -6 = 0
0 + 9x + -12y = 0 + -6
9x + -12y = 0 + -6

Combine like terms: 0 + -6 = -6
9x + -12y = -6

Add '12y' to each side of the equation.
9x + -12y + 12y = -6 + 12y

Combine like terms: -12y + 12y = 0
9x + 0 = -6 + 12y
9x = -6 + 12y

Divide each side by '9'.
x = -0.6666666667 + 1.333333333y

Simplifying
x = -0.6666666667 + 1.333333333y

See similar equations:

| 3s-62=s | | 5p-60=p-4 | | n-8-1=-13 | | -5-7k+8k=0 | | x=2x-70 | | -12a-5b=27 | | 3z=z+26 | | r/320 | | 4n-2n+4=1+17 | | 4v-3+8=13 | | -1/2w-7/5=4/3 | | 3+3(2-6)squared= | | -8a-2a=-10 | | b+4=2b-3 | | -x-8=x+2 | | -4(5x-4)+3(4x+2)= | | 6n-3=3n-15 | | 2(2x+2)-3(x-4)= | | A/2=36 | | 84=78+n | | -x+7x=-12 | | -x^2+5=(4x-1)(4x-1) | | 4a+7a=7a+16 | | v/-4=13 | | -0.25+0.6= | | -0.25-0.6= | | (13m-11)=2m+5 | | -6(b-6)+4=88 | | 4.5s-s= | | 0.25-0.6= | | x*3+75=x*9-9 | | 18x11/(18x11)= |

Equations solver categories